Dfesnippets: An open-source library for dataflow acceleration on FPGAs - Grigoras,P; Burovskiy,P; Arram,J; Niu,X; Cheung,K; Xie,J; Luk,W (Springer, 2017)
Highly-tuned FPGA implementations can achieve significant performance and power efficiency gains over general purpose hardware. However the limited development productivity has prevented mainstream adoption of FPGAs in many areas such as High Performance Computing. High level standard development libraries are increasingly adopted in improving productivity. We propose an approach for performance critical applications including standard library modules, benchmarking facilities and application benchmarks to support a variety of usecases. We implement the proposed approach as an open-source library for a commercially available FPGA system and highlight applications and productivity gains.